Accountability of the Investigators of the Indonesian National Police and Legal Remedies Taken by the Suspect in the Event of an Error in Persona - Nurhaisyah Nurhaisyah; Irabiah Irabiah; La Ode Awal Sakti; Basrawi Basrawi; Muhammad As Ari. AM (Faculty of Law, Universitas Sembilanbelas November Kolaka, 2025)
The arrest procedure has been regulated in the Criminal Procedure Code. However, in practice, it is possible that in the arrest process there may be wrongful arrests. In legal terms, wrongful arrests made by police investigators are called errors in persona. The purpose of this study is to determine the accountability of police investigators when making wrongful arrests based on the law and legal remedies carried out by suspects in the event of an error in persona. In this study, the author used a normative research method which is research conducted by literature study or document study. The data analysis technique used is a qualitative normative analysis, namely by interpreting or drawing conclusions about the legal materials that have been processed. The results of the study show that the responsibility of police investigators when making wrongful arrests based on the law can be in the form of civil liability, criminal liability, and ethical and administrative liability. The legal remedies taken by the suspect in the event of an error in persona are in the form of pretrial legal remedies which are judicial legal remedies, and the victim of wrongful arrest can also take non-judicial legal remedies (out-of-court settlement) in the form of a complaint to the National Human Rights Commission (Komnas HAM), or a complaint to the nearest Police Service Center (SPK).